Peranan Advokat sebagai Mediator di Pengadilan Agama Dalam Perspektif Maslahah Mursalah - Wiwied Sekar Arum; Ade Yusrah Hasanah; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Advocate is a law enforcement and free, independent and responsible job in enforcing the law guaranteed by law for the implementation of effort to upload the rule of law. According to Law No, 16 Year 2003 concerning Advocates, insisted that, Advocate is a person who is providing legal services both inside and outside the court that meets the requirements in accordance with applicable regulations. The legal sevices provided by advocates include providing legal consultations, legal assistance, exercising power of attorney, representing, accompanying, defending, and carrying out otjer legal actions in the in the interests of clients. Everyone with the title of advocate must always try to improve the quality of service to the community because advocates are the link between society and the state.Advocate as law enforcement officer also play a role as mediators who assist the mediation process in court.The research method that the authors use is a normative juridical approach.The authority of an advocate practicing in a religious court is the same as an advocate practicing in a general court.The existence of an advocate has an important meaning in providing a solution to the problems faced by someone, especially thos who practice in religious courts. Keywords : Advocate Role, Mediators,Maslahah Mursalah